Michael Jackson : King of Pop, 1958-2009 - Herbert, Emily (Solon, Ohio Playaway Digital Audio, 2009)
This biography traces the rise of the man, from child prodigy to tortured megastar. It is the definitive portrait of a pop legend whose strange and brilliant life will never be forgotten.
Include Index and Illustrations
Keywords: Singers